The Impact of Construction 4.0 on Project Efficiency and Safety - Dewi, Kemmala; Krisdiyanto, Aris; Dewanto, Dewanto; Santosa, Tomi Apra (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the influence of construction 4.0 on project efficiency and safety. This type of research is a quantitative research with a meta-analysis approach. The data sources in this study come from the analysis of 13 national and international journals published in 2022-2025. The inclusion criteria are that the research must be relevant; research obtained from the database of reputable journals Sciencedirect; Wiley, Springer, Google Scholar and Mendeley, Research should report complete data. Analyze data with the help of Microsoft Excel and Jamovi applications. The results of this study explain the value of the summary effect size of ( d = 0.830 ; z = 6.073 ; p < 0.001). These findings show that construction 4.0 has a positive influence on the efficiency and safety of project work with a high influence category.